Introduction of the Research Network of Defined Population Affiliated by the Social Determinants of Health Research Center of Shahid Beheshti University of Medical Sciences: Structure and Start up Methodology - Ali-Asghar Kolahi (Shahid Beheshti University of Medical Sciences, 2014)
Background and Objective: A defined population is needed to determine the potential needs of society, calculate the correct indicators in the suitable time & health care activities and to do the population based study. It is also needed to provide the required education for training, to perform the educational program and intervention in promoting healthy lifestyles. In addition, a defined population is required for screening and treatment, implementing the referral system and to determine the optimal service. The aim of this study is to introduce the structure and start-up methodology of the research network of a defined population, affiliated by the social determinants of health research center of Shahid Beheshti University of Medical Sciences. Materials and Methods: The project started by choosing 10 health centers of 10 different areas in 2012. Two new centers have been added during years 2013 and 2014. Now the number of the covered population, by the network, has reached to 40000 people. The covered population is chosen based on the characters representing the total population of Tehran city.